Reconstructing the palaeoenvironment at the early Mesolithic site of Lake Duvensee: Ground-penetrating radar and geoarchaeology for 3D facies mapping. (June 2020) - Corradini, Erica; Wilken, Dennis; Zanon, Marco; Groß, Daniel; Lübke, Harald; Panning, Diana; Dörfler, Walter; Rusch, Katharina; Mecking, Rebekka; Erkul, Ercan; Pickartz, Natalie; Feeser, Ingo; et al.
We investigate the landscape development of the early Mesolithic hunter-gatherer sites of Duvensee (10000–6500 cal. BCE). Based on ground-penetrating radar (GPR) and geoarchaeological drillings, we present for the first time a three-dimensional (3D) reconstruction of the palaeoenvironment of 63 ha covering subarea of the former lake during the Mesolithic. The archaeological aims were (1) to detect the location of former islands possibly hosting hunter-gatherer settlements and (2) to reconstruct the ancient landscape development for understanding prehistoric land use. The research in Duvensee lasts almost 100 years, providing vivid illustrations of early Mesolithic life. Clusters of Mesolithic camps have been found located on small sand hills that formed islands in the prehistoric lake. For this environment, we present depth maps of the three most important sedimentary facies interfaces of the ancient Lake Duvensee. Interface1 represents the transition between coarse organic sediments (peat and coarse detritus gyttja) and fine-grained organic sediments (fine detritus gyttja, calcareous gyttja), Interface2 represents the transition to the underlying clayish-loamy sediments, and Interface3 marks the top of the basal sand deposits at the lake bottom. From Interface3, we identified the location and extent of five former islands with Mesolithic camps. Stratigraphic information from the corings enabled us to create a 3D model of the spatio-temporal development of the Duvensee bog. The locations of the islands and their estimated dive-up times agree with the spatio-temporal pattern of the previous archaeological finds. The model shows where hunter-gatherers could settle and move from one island to another following the shorelines of the overgrowing lake. The 3D stratigraphic model provides growth and shrinking rates of the island and lake areas in the Mesolithic, and volumes of organic and non-organic deposited lake sediments. Besides, it provides a basis for a sustainable groundwater management needed for heritage preservation.